Interface conversion between CCITT recommendations X.21 and V.24 - Van der Harst, Hubert (Department of Electrical Engineering, 2016)
The subject of this thesis concerns conversion between the interfaces specified by CCITT recommendations X.21 and V.24. The evolution of public data networks against the background of data communications using the telephone network is outlined. The DTE/DCE interface is identified as being of particular importance and is explained in terms of the ISO model for Open Systems interconnection (OSI). CCITT recommendation X.21 is described in detail using the OSI layered approach. Finite state machine (FSM) terminology is defined and the concept of an interface machine introduced. CCITT recommendation V.24 is described in terms of the physical layer of the OSI model. Only those aspects of V.24 relevant to the subject of this thesis are examined. Interface conversion between X.21 and V.24 is discussed in detail and the design of devices to perform the conversion described. A microprocessor-based translator to perform interface conversion between a V.24 DTE and a X.21 DCE for switched circuit use is designed, using the FSM approach. A preliminary model of such a translator, implemented on a development system, is described. Its hardware and software are outlined and areas for further work identified.